Πολιτικὲς ἐπιπτώσεις τῆς ἀγροτικῆς μεταρρύθμισης καὶ ὁ νέος ρόλος τοῦ κράτους στὸν Μεσοπόλεμο - Αλβανός, Ραϋμόνδος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
The article focuses on interwar Greece after the exchange of populations with Turkey in 1923. The arrival of 1, 2 million refugees to a state of about only 5 million people deeply affected Greek economy, society and politics. One significant change was the expansion of the state and its institutions so as to respond effectively to the survival needs of the refugees. The state became much more important to the everyday life of the Greeks when it initiated the confiscation of large land properties, which were given to landless local and refugee peasants. This agrarian reform had major effects on Greek politics since small landowners allied with the ruling political elite, represented by the two major parties of the era, the Venizelists and Antivenizelists. By voting en masse for these two parties, the farmers showed only minimum support for the communist or the agrarian political party, demonstrating their faith in democracy and parliamentarism. Agrarian reform in combination with pro-farmers measures (massive loans of the banks and substantial tax reduction) greatly benefited the landowners. On the other hand, excessive lending and the fact that the farmers had not been given their final titles of ownership made them dependent on the politicians. However, the latter needed their vote, so they did everything they could to help them overcome their difficulties. Banks, jurisdiction, police and other state institutions were controlled by the politicians who were elected by the farmers. The result was a lack of class conflict, a situation which contrasted sharply with the major Greek cities, where bloody confrontations between police and workers often happened. The mutual interdependence between politicians and farmers helped maintain social cohesion and parliamentary democracy until 1936, when the King of Greece approved the establishment of a dictatorship under Ioannis Metaxas.